Reversal of ABCB1-related multidrug resistance by ERK5-IN-1 - Fang Wang (Journal of Experimental & Clinical Cancer Research, 2020)
Abstract Background Inhibition of ABC transporters is considered the most effective way to circumvent multidrug resistance (MDR). In the present study, we evaluated the MDR modulatory potential of ERK5-IN-1, a potent extracelluar signal regulated kinase 5 (ERK5) inhibitor. Methods The cytotoxicity and MDR reversal effect of ERK5-IN-1 were assessed by MTT assay. The KBv200-inoculated nude mice xenograft model was used for the in vivo study. Doxorubicin efflux and accumulation were measured by flow cytometry. The modulation of ABCB1 activity was measured by colorimetric ATPase assay and [125I]-iodoarylazidoprazosin (IAAP) photolabeling assay. Effect of ERK5-IN-1 on expression of ABCB1 and its downstream markers was measured by PCR and/or Western blot. Cell surface expression and subcellular localization of ABCB1 were tested by flow cytometry and immunofluorescence. Results Our results showed that ERK5-IN-1 significantly increased the sensitivity of vincristine, paclitaxel and doxorubicin in KBv200, MCF7/adr and HEK293/ABCB1 cells, respectively. This effect was not found in respective drug sensitive parental cell lines. Moreover, in vivo combination studies showed that ERK5-IN-1 effectively enhanced the antitumor activity of paclitaxel in KBv200 xenografts without causing addition toxicity. Mechanistically, ERK5-IN-1 increased intracellular accumulation of doxorubicin dose dependently by directly inhibiting the efflux function of ABCB1. ERK5-IN-1 stimulated the ABCB1 ATPase activity and inhibited the incorporation of [125I]-iodoarylazidoprazosin (IAAP) into ABCB1 in a concentration-dependent manner. In addition, ERK5-IN-1 treatment neither altered the expression level of ABCB1 nor blocked the phosphorylation of downstream Akt or Erk1/2. No significant reversal effect was observed on ABCG2-, ABCC1-, MRP7- and LRP-mediated drug resistance. Conclusions Collectively, these results indicated that ERK5-IN-1 efficiently reversed ABCB1-mediated MDR by competitively inhibiting the ABCB1 drug efflux function. The use of ERK5-IN-1 to restore sensitivity to chemotherapy or to prevent resistance could be a potential treatment strategy for cancer patients.